Anatomy and physiology[videorecording] the muscular system - Cooper, Mark; Cooper, Mark; Cooper, Mark; Cooper, Mark (CTI Production, Inc., 2005)
Provide a fundamental understanding of the Muscular System that will be useful to those in a biomedical field.